How does the globalization process improve population health? An analysis from the perspective of economic complexity - Chen, Qianxue; Zhu, Xinzhe; Yang, Lihua; Gu, Wenbo (Frontiers in Public Health, 2025)
IntroductionThe comprehensive connectivity brought about by globalization and the health of local populations exhibit a contradictory relationship, which has become increasingly complex, especially since the COVID-19 pandemic. This study aims to introduce a new perspective of economic complexity to explore the complex relationship between globalization and population health at the economic level.MethodsUsing an unbalanced panel dataset from 179 countries/regions between 1995 and 2021, this study investigates the mechanisms and contextual conditions linking globalization to population health from the perspective of economic complexity.ResultsOur results suggest that globalization is generally associated with improved health outcomes, whereas economic globalization, when viewed in a subdimensional manner, shows a negative correlation with population health. By framing economic complexity as a proxy variable for local production capacity or industrial structure, this study offers preliminary evidence on how globalization interacts with structural economic factors to shape health outcomes. Specifically, considering the economic structure as an influence channel, economic complexity plays a mechanistic role in the relationship between globalization and health, with higher complexity outlook levels potentially strengthening the positive association.DiscussionThese findings, while subject to the limitations of cross-country aggregated data, provide insights for policymakers to balance global integration with health system preparedness.